Experimental Study of I-V Characteristics Dye Sensitizer Solar Cell Based on Carotenoid and Photoelectrode TiO2 - Boisandi (Program Studi Pendidikan Fisika, Fakultas Pendidikan MIPA & Teknologi, Universitas PGRI Pontianak, 2025)
Dye sensitizer solar cell (DSSC) is one of the photoelectrochemical cells consisting of photoelectrode, dye, electrolyte, and counter electrode. This article presents experimental data of I-V characteristics of DSSC made from carotenoid and photoelectrode TiO2. Optimization of carotenoid concentration in ethanol and optimization of TiO2 concentration in slipcasting method were investigated. It was found that TiO2 concentration gave significant effect in slipcasting method. Current-voltage (I-V) characteristics of DSSC made from carotenoid produced open circuit voltage (VOC) of 480 mV, short circuit current density (JSC) of 28 μA/cm2, Fill Factor (FF) = 0.37 and photoelectric conversion efficiency (η) 5.07 × 10-3%.